INTERVENSI MULLIGAN MOBILIZATION WITH MOVEMENTLEBIH BAIK DARISEMISQUAT EXERCISEDALAM MENINGKATKAN FUNGSIONAL SENDI LUTUT PADA KASUS CHONDROMALACIA PATELLA - Maksimus Bisa (Jurnal Dinamika Pendidikan, 2018)
ABSTRACT This study is to determine the difference in intervention of mulligan mobilization with movement with anemia in exercise to improve the functional knee joint in the case of chondromalacia patella. This research was conducted at the Sukmajaya Physio Clinic in East Depok from April to July 2018. Methods: This study was quasi-experimental with a comparative approach to pre and post test group control design with a sample of 30 people, where sampling was done with allocation random sampling that met the inclusion criteria. Samples were grouped into two groups, namely treatment group I consisting of 15 people given intervention mulligan mobilization with movement and ultra sound and treatment group II consisting of 15 people given semisquat exercise dan ultra sound. Data analysis: using statistical tests. The results of the normality and homogeneity test of the two groups showed normal distribution and homogeneous data with a value of Ï> 0.05. The research hypothesis test was conducted by independent simple t-test comparative test using the difference between lower extremity functional scale (LEFS) and test stand between the treatment groups with treatment group II after intervention, it got Ï = 0.023. Results: There were significant differences in the combination intervention of Mulligan Mobilization With Movement and ultrasound with a combination of Semi-squat exercise and ultrasound on functional improvement of the knee in the case of chondromalacia patella. Keywords: mulligan mobilization, squat exercise, and chondromalacia patella. ABSTRAK Penelitian ini bertijuan untuk mengetahui perbedaan intervensi mulligan mobilization with movementdengansemisquat exercisedalam meningkatkan fungsional sendi lutut pada kasus chondromalacia patella. Penelitian ini dilaksanakan di Klinik Fisio Sukmajaya Depok Timur bulan April hingga Juli 2018. Metode: penelitian ini bersifat quasi experimental dengan pendekatan komparatif pre dan post test group control design dengan jumlah sampel 30 orang, dimana pengambilan sampel dilakukan dengan allocationrandom sampling yang memenuhi kriteria inklusi. Sampel dikelompokkan menjadi dua kelompok yaitu kelompok perlakuan I terdiri dari 15 orang diberikan intervensi mulligan mobilization with movementdan ultra sounddan kelompok perlakuan II terdiri dari 15 orang diberikan semisquat exercisedan ultra sound. Analisis data: menggunakan uji statistik. Hasil uji normalitas dan homogenitas kedua kelompok menunjukkan data berdistribusi normal dan homogendengan nilai Ï > 0,05.Uji hipotesis penelitian dilakukan dengan uji komparasi independent simple t-testmenggunakan data selisih nilai lower extremity functional scale (LEFS)dan strok blance stand testantara kelompok perlakuan I dengan kelompok perlakuan II sesudah intervensididapatkan Ï = 0,023. Hasil penelitian:ada perbedaan yang signifikan intervensi kombinasi Mulligan Mobilization With Movement dan ultrasound dengan kombinasi Semi squat exercise dan ultrasound terhadap peningkatan fungsional lutut pada kasus chondromalacia patella. Kata kunci: mulligan mobilization, squat exercise, dan chondromalacia patella.